Influences of Aluminium / E-Glass Volume Fraction on Flexural and Impact Behaviour of GLARE Hybrid Composites - Santhosh M. S.; Sasikumar R. (Журнал інженерних наук)
Composites with different configuration of fiber (E-Glass) and metal (Aluminium) laminates were fabricated and tested for grasping optimum hybrid structure. GLARE (Glass laminate aluminium reinforced epoxy) is a unique composite recently being used by wide engineering domains like defense body and vehicle armors, aerospace, marine and structural applications. The GLARE hybrid composites are manufactured by adding very thin layer of aluminium sheets (surface treated) on the surface of unidirectional E-Glass fiber fabrics in presence of epoxy polymer. Firstly three hybrid GLARE laminates were fabricated with different volume fractions. Consequently, impact and flexural behaviors are measured by izod, charpy impact and flexural tests for all volume configurations. Impact resistance of such hybrid laminate is intensively great. The results depicts that the linear metal volume fraction (MVF) increment on fiber metal laminates greatly increases impact energy absorption capacity of composites and little difference in flexural modulus. Finally the fractured surfaces were analyzed by optical microscope.